Screening of esophageal varices by esophageal capsule endoscopy: results of a French multicenter prospective study - Sacher-Huvelin, Sylvie; Calès, Paul; Bureau, Christophe; Valla, Dominique; Vinel, Jean Pierre; Duburque, Clotilde; Attar, Alain; Archambeaud, Isabelle; Benamouzig, Robert; Gaudric, Marianne; Luet, Dominique; Couzigou, Patrice; Planche, Lucie; Galmiche, Jean Paul; Coron, Emmanuel (Endoscopy, 2015)
Background and study aim: Esophageal video capsule endoscopy (ECE) is a new technique that allows examination of the esophagus using a noninvasive approach. The aim of this study was to compare ECE with esophagogastroduodenoscopy (EGD) for the diagnosis of esophageal varices in patients with cirrhosis.Patients and methods: A total of 330 patients with cirrhosis and with no known esophageal varices were prospectively enrolled. Patients underwent ECE first, followed by EGD (gold standard). The endoscopists who performed EGD were blind to the ECE result. Patient satisfaction was assessed using a visual analog scale (maximum score 100).Results: A total of 30 patients were excluded from the analysis because they did not undergo any endoscopic examinations. Patients (mean age 56 years; 216 male) had mainly alcoholic (45 %) or viral (27 %) cirrhosis. The diagnostic indices of ECE to diagnose and correctly stage esophageal varices were: sensitivity 76 % and 64 %, specificity 91 % and 93 %, positive predictive value 88 % and 88 %, and negative predictive value 81 % and 78 %, respectively. ECE patient satisfaction scored significantly higher than EGD (87 ± 22 vs. 58 ± 35; P < 0.0001).Conclusions: ECE was well tolerated and safe in patients with liver cirrhosis and suspicion of portal hypertension. The sensitivity of ECE is not currently sufficient to replace EGD as a first exploration in these patients. However, due to its excellent specificity and positive predictive value, ECE may have a role in cases of refusal or contraindication to EGD. ECE might also improve compliance to endoscopic follow-up and aid important therapeutic decision making in the prophylaxis of bleeding. Trial registration: EudraCT (ID RCB 2009-A00532-55) and ClinicalTrials.gov (NCT00941421).